2013
DOI: 10.1016/j.gmbhs.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-induced alteration in reproductive profile and its amelioration by the polyherbal formulation MTEC (modified) in streptozotocin-induced diabetic albino rats

Abstract: This study investigated oxidative stress-mediated alterations in the reproductive profile of streptozotocin-induced diabetic albino rats and their amelioration by the polyherbal formulation MTEC (modified), constituted with n-hexane fractions of hydromethanol extracts of Musa paradisiaca roots, Tamarindus indica seeds, Eugenia jambolana seeds, and Coccinia indica leaves in a specific ratio. We noted a change in serum insulin levels and a modulation in carbohydrate metabolic parameters, i.e. increased fasting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 46 publications
7
26
0
Order By: Relevance
“…However, Mallick et al (2007), Chatterjee et al (2012Chatterjee et al ( , 2013, Hajizadeh et al (2014) and Shah and Khan (2014) reported a recovery compared to untreated diabetic animals. According to Chatterjee et al (2013), the extract used for treatment of diabetic animals increased the production of the transforming growth factor β1 (TGF-β1) which prevents the infiltration of lymphocytes in pancreatic islet and protects β-cells while providing a safe environment for cellular regeneration.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…However, Mallick et al (2007), Chatterjee et al (2012Chatterjee et al ( , 2013, Hajizadeh et al (2014) and Shah and Khan (2014) reported a recovery compared to untreated diabetic animals. According to Chatterjee et al (2013), the extract used for treatment of diabetic animals increased the production of the transforming growth factor β1 (TGF-β1) which prevents the infiltration of lymphocytes in pancreatic islet and protects β-cells while providing a safe environment for cellular regeneration.…”
Section: Resultsmentioning
confidence: 91%
“…In spite of the absence of testicular weight in such studies, the reduction of GSI, or rather, the percentage of body weight allocated in the gonads, indicated a decrease in testis size. Specifically in Chatterjee et al (2013), in which body weight of experimental groups had no significant difference, the reduction of such index features drastic testicular damage. Wankeu-Nya et al (2013) also observed a testicular atrophy in diabetes-induced animals, partially recovered by treatment.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations